Risk factors for hand-wrist disorders in repetitive work. Issue 8 (26th March 2007) - Thomsen, J F; Mikkelsen, S; Andersen, J H; Fallentin, N; Loft, I P; Frost, P; Kaergaard, A; Bonde, J P; Overgaard, E
Abstract : Objectives: To identify the risk of hand-wrist disorders related to repetitive movements, use of hand force and wrist position in repetitive monotonous work. Methods: Using questionnaires and physical examinations, the prevalence and incidence of hand-wrist pain and possible extensor tendonitis (wrist pain and palpation tenderness) were determined in 3123 employees in 19 industrial settings. With the use of questionnaires and video recordings of homogenous work tasks number of wrist movements, hand force requirements and wrist position were analysed as risk factors for hand-wrist disorders, controlling for potential personal and psychosocial confounders. All participants were re-examined three times during a follow-up period of three years. Results: Force but not repetition and position was related to hand-wrist pain and possible tendonitis in the baseline analyses showing an exposure-response pattern. Odds ratios for the risk of hand pain was 1.7 (95% CI 1.3 to 2.2) and for possible tendonitis 1.9 (95% CI 1.1 to 3.3). There was no significant interaction between the ergonomic factors. In the follow-up analyses force remained a risk factor for hand pain (OR 1.4, 95% CI 1.1 to 1.8) and for possible tendonitis (OR 2.9, 95% CI 1.3 to 6.8). Repetition was also a risk factor for the onset of hand-wrist pain (OR 1.6, 95% CI 1.2 to 2.3). Conclusions: Increasing levels of force were associated with prevalent and incident hand-wrist pain and possible extensor tendonitis. The results for repetition were less consistent. Working with the hand in a non-neutral position could not be identified as a risk factor.